RUMAH FESYEN BERKELANJUTAN DI BANDUNG DENGAN PENDEKATAN EKOLOGI, SIMBIOSIS DAN METAFORA - Tjut Nabilla Zafriana; Rudy Trisno (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
With the increase in human needs caused by the development of the human population, various phenomena arise. Textiles, as one of the needs of the community that are used as clothing, also continue to increase. The development of the times and trends that are constantly updated, give rise to the phenomenon of fast fashion and consumptive culture which causes the accumulation of fashion waste. The Sustainable Fashion House project in Bandung aims to develop recycled fashion products and also reduce consumptive nature by improving clothes according to current trends by elevating localities that are almost extinct. The method used is the symbiotic method and the metaphor of the scarf with a Sundanese neo-vernacular architectural approach. The conclusion is to accommodate all fashion recycling activities into something of high value. In addition, it also invites the public and the fashion community to accommodate and process used clothes so that they can be resold as well as for themselves. The novelty of this project is to provide a platform for the general public of Bandung to manage various activities related to fashion. Keywords:  Ecology; Fashion; Metaphor; Neo-Vernacular; Symbiosis Abstrak Dengan meningkatnya kebutuhan manusia yang disebabkan dengan perkembangan populasi manusia, muncul berbagai fenomena. Tekstil, sebagai salah satu kebutuhan masyarakat yang digunakan sebagai pakaian juga terus meningkat. Perkembangan zaman dan tren yang terus diperbarui, memunculkan fenomena fast fashion dan budaya konsumtif yang menyebabkan menumpuknya limbah fesyen. Proyek Rumah Fesyen Berkelanjutan di Bandung ini bertujuan untuk mengembangkan hasil fesyen daur ulang dan juga mengurangi sifat konsumtif dengan memerbaiki baju menyesuaikan tren yang saat itu terjadi dengan mengangkat lokalitas yang hampir punah. Metode yang digunakan adalah metode simbiosis dan metafora dari selendang dengan pendekatan arsitektur neo-vernakular Sunda. Kesimpulannya adalah mewadahi segala kegiatan daur ulang fesyen menjadi sesuatu hal yang bernilai tinggi. Selain itu juga mengajak masyarakat dan komunitas fesyen untuk menampung dan mengolah pakaian bekas sehingga dapat dijual kembali maupun untuk dirinya sendiri. Kebaruan proyek ini adalah memberikan wadah untuk masyarakat umum Bandung untuk mengelola berbagai kegiatan yang berhubungan dengan fesyen.